The Role of Deep Learning in Developing Inclusive and Multicultural Education in Indonesian Junior High Schools - Zainuddin Zainuddin; Ahmad Rojali; Anis Susanti (Mathematics Education Study Program, 2025)
This article aims to examine the role of the deep learning model in fostering inclusive and multicultural education in Indonesian junior high schools. Using a literature review approach, the discussion focuses on the essence of deep learning as a comprehensive instructional method that emphasizes conceptual understanding, critical reflection, and meaningful connections in real-world contexts. The study finds that this approach holds significant potential in accommodating students’ diverse backgrounds and promoting cross-cultural understanding. By integrating the principles of inclusion and multiculturalism, deep learning can serve as a strategic framework for realizing transformative, contextual, and equitable learning. This article also presents a conceptual model of inclusive-multicultural learning based on deep learning, which can be adapted to the context of junior high schools in Indonesia.